Spatial Dimensions of Trade Liberalization and Economic Convergence : Mexico 1985-2002 - Aroca, Patricio (Oxford University Press on behalf of the World Bank, 2013)
This article employs established techniques from the spatial economics literature to identify regional patterns of income and growth in Mexico and to examine how they have changed over the period spanned by trade liberalization and how they may be linked to the income divergence observed following liberalization. The article first shows that divergence has emerged in the form of several income clusters that only partially correspond to traditional geographic regions. Next, when regions are defined by spatial correlation in incomes, a south clearly exists, but the north seems to be restricted to the states directly on the United States (U.S.) border and there is no center region. Overall, the principal dynamic of both the increased spatial dependency and the increased divergence lies not on the border but in the sustained underperformance of the southern states, starting before the North American free-trade agreement, and to a lesser extent in the superior performance of an emerging convergence club in the north-center of the country.